Fungal Communities Including Plant Pathogens in Near Surface Air Are Similar across Northwestern Europe - Nicolaisen, Mogens; West, Jonathan S.; Sapkota, Rumakanta; Canning, Gail G. M.; Schoen, Cor; Justesen, Annemarie F. (Frontiers in Microbiology, 2017)
Information on the diversity of fungal spores in air is limited, and also the content of airborne spores of fungal plant pathogens is understudied. In the present study, a total of 152 air samples were taken from rooftops at urban settings in Slagelse, DK, Wageningen NL, and Rothamsted, UK together with 41 samples from above oilseed rape fields in Rothamsted. Samples were taken during 10-day periods in spring and autumn, each sample representing one day of sampling. The fungal content of samples was analyzed by metabarcoding of the fungal internal transcribed sequence 1 (ITS1) and by qPCR for specific fungi. The metabarcoding results demonstrated that season had significant effects on airborne fungal communities. In contrast, location did not have strong effects on the communities, even though locations were separated by up to 900 km. Also, a number of plant pathogens had strikingly similar patterns of abundance at the three locations. Rooftop samples were more diverse than samples taken above fields, probably reflecting greater mixing of air from a range of microenvironments for the rooftop sites. Pathogens that were known to be present in the crop were also found in air samples taken above the field. This paper is one of the first detailed studies of fungal composition in air with the focus on plant pathogens and shows that it is possible to detect a range of pathogens in roof-top air samplers using metabarcoding.